Australia and the Middle East a front-line relationship - Mansouri, Fethi (Library of international relations, 2006)
Australia's encounters with the Middle East have historically been defined initially through its membership of the British Empire, later as a key Commonwealth player and more recently through Australia's close strategic relationship with the US. The book seeks to draw together the various dimensions and themes of this relationship - from trade and migration, to Australia's increasing strategic interest and current military involvement in the region.